2023
DOI: 10.3389/fmed.2022.952159
|View full text |Cite
|
Sign up to set email alerts
|

Suggesting a mechanism for acupuncture as a global percutaneous needle fasciotomy that respects tensegrity principles for treating fibromyalgia

Abstract: Acupuncture is a minimally invasive therapeutic method that uses small caliber needles while inserting them through the skin into various areas of the body. Some empirical studies find evidence to support the use of acupuncture as a treatment for certain medical conditions, however, this peculiar practice is widely considered as the domain of alternative and non-evidence-based medicine. Several mechanisms have been suggested in an attempt to explain the therapeutic action of acupuncture, but the way in which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 133 publications
0
8
0
Order By: Relevance
“…Globally, the long COVID-19 wave has risen and is leading to extensive morbidity, decreased quality of life, and suffering in society. SARS-CoV-2 infection can lead to pro-inflammatory and pro-fibrotic responses in multiple tissues, including myofascial tissue, and leads to fibrosis and upregulation of The positive feedback loop of fascial armoring (fascial rigidity and tensegrity tension) with inputs into the vicious cycle of myofibroblasts [adapted for long COVID-19 from Figure 3 in Plaut (2023) (7)]. Fibroblasts, adipocytes, and other cell-types can differentiate to myofibroblasts (the intermediate proto-myofibroblast phenotype is not shown here).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Globally, the long COVID-19 wave has risen and is leading to extensive morbidity, decreased quality of life, and suffering in society. SARS-CoV-2 infection can lead to pro-inflammatory and pro-fibrotic responses in multiple tissues, including myofascial tissue, and leads to fibrosis and upregulation of The positive feedback loop of fascial armoring (fascial rigidity and tensegrity tension) with inputs into the vicious cycle of myofibroblasts [adapted for long COVID-19 from Figure 3 in Plaut (2023) (7)]. Fibroblasts, adipocytes, and other cell-types can differentiate to myofibroblasts (the intermediate proto-myofibroblast phenotype is not shown here).…”
Section: Discussionmentioning
confidence: 99%
“…Movement might help release fascial tensions by various mechanisms ( 4 ) and immobility leads to fibrosis and increase in myofibroblasts ( 4 , 133 ). Needling therapy (when done correctly) is expected to modulate the disease course because of its suggested effects on the bio-tensegrity system ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are no diagnostic criteria for PASC, but some symptoms resemble those of bromyalgia (FM), a chronic disorder characterized by hyperalgesia and muscle weakness without a speci c location 9 . FM is listed by the CDC as one of the conditions sharing symptoms with PASC 10 and recent studies showed that 30-40% of individuals with PASC meet the American College of Rheumatology (ACR) FM diagnostic criteria 11,12 . FM's underlying cause has not been proven, but it is hypothesized to involve sensory sensitization of the spinothalamic tract, possibly attributed to microglial overactivation by numerous factors, including viral infections [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%